Pregnancy Outcomes of Managed Medicaid Members Prescribed Home Administration of 17 α-Hydroxyprogesterone Caproate - Lucas, Brad; Poole-Yaeger, Amy; Istwan, Niki; Stanziano, Gary; Rhea, Debbie; Mason, Mary (American Journal of Perinatology, 2012)
Objective Examine adherence to treatment guidelines and rates of recurrent spontaneous preterm birth (SPTB) in managed Medicaid patients prescribed 17 α-hydroxyprogesterone caproate (17P).Study Design A retrospective observational study of women receiving 17P between July 2004 and May 2010 through one of Centene's managed Medicaid programs. Included for analysis were singleton pregnancies without cerclage having SPTB history and prescribed 17P by their physician. Compounded 17P was administered through an outpatient program inclusive of patient education, weekly home nurse visits, and 24-7 telephonic nurse access. A health plan–directed pregnancy management program, Start Smart for Your Baby®, supported the therapy with case management activities.Results Of the 790 patients studied, 58.6% initiated 17P in the recommended 16- to 20.9-week gestational age window. Elective discontinuation of 17P occurred in 18.6%. Of the 10,583 17P injections administered, 97.5% were administered within the recommended injection interval of 6 to 10 days. Recurrent SPTB occurred in 28.2% of women studied.Conclusion Managed Medicaid patients enrolled in an outpatient 17P administration program supported with maternal case management have high rates of treatment compliance. Their pregnancy outcomes compare favorably to previously published reports that include both Medicaid and commercially insured patients.
Keywords: 17 alpha-hydroxyprogesterone caproate (17P); recurrent spontaneous preterm birth; Medicaid; managed care; case management